Laboratory Stock Variants of the Archetype Silver Resistance Plasmid pMG101 Demonstrate Plasmid Fusion, Loss of Transmissibility, and Transposition of Tn7/pco/sil Into the Host Chromosome - Hooton, Steven P.T.; Pritchard, Alexander C.W.; Asiani, Karishma; Gray-Hammerton, Charlotte J.; Stekel, Dov J.; Crossman, Lisa C.; Millard, Andrew D.; Hobman, Jon L. (Frontiers in Microbiology, 2021)
Salmonella Typhimurium carrying the multidrug resistance (MDR) plasmid pMG101 was isolated from three burns patients in Boston United States in 1973. pMG101 was transferrable into other Salmonella spp. and Escherichia coli hosts and carried what was a novel and unusual combination of AMR genes and silver resistance. Previously published short-read DNA sequence of pMG101 showed that it was a 183.5Kb IncHI plasmid, where a Tn7-mediated transposition of pco/sil resistance genes into the chromosome of the E. coli K-12 J53 host strain had occurred. We noticed differences in streptomycin resistance and plasmid size between two stocks of E. coli K-12 J53 pMG101 we possessed, which had been obtained from two different laboratories (pMG101-A and pMG101-B). Long-read sequencing (PacBio) of the two strains unexpectedly revealed plasmid and chromosomal rearrangements in both. pMG101-A is a non-transmissible 383Kb closed-circular plasmid consisting of an IncHI2 plasmid sequence fused to an IncFI/FIIA plasmid. pMG101-B is a mobile closed-circular 154 Kb IncFI/FIIA plasmid. Sequence identity of pMG101-B with the fused IncFI/IncFIIA region of pMG101-A was >99%. Assembled host sequence reads of pMG101-B showed Tn7-mediated transposition of pco/sil into the E. coli J53 chromosome between yhiM and yhiN. Long read sequence data in combination with laboratory experiments have demonstrated large scale changes in pMG101. Loss of conjugation function and movement of resistance genes into the chromosome suggest that even under long-term laboratory storage, mobile genetic elements such as transposons and insertion sequences can drive the evolution of plasmids and host. This study emphasises the importance of utilising long read sequencing technologies of plasmids and host strains at the earliest opportunity.